Regarding letters, cells, them and teachers-in-process (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
These letters, written by two authors, commemorate and reflect on the work developed by the authors with incarcerated women at the Presidio Regional de Joinville (PRJ). The texts document the initial research project and mounting of the play celas in 2010, created from narratives of women in prison and those released from PRJ, as well as the theater workshops held with these women years later. This is interspersed with scenes from the play in its first version and later production. This text weaves together the threads of acting and analysis. Through performative writing, it seeks to mix memories and feelings of artist-teachers with narratives and reflections on the pedagogical process developed in the second half of 2019 at PRJ, from a gendered perspective. The paper divulges the hopes, uncertainties, discoveries, frustrations and achievements that this path has brought, focusing on the perception of teaching as a constant and dialogical creative process, of teachers-in-process.
Keywords: Theatre pedagogy; Theatre with women in deprivation of liberty; Teachers-in-process; Feminist critical theory